Kajian Tahap Kesedaran Kakitangan Universiti Tun Hussein Onn Malaysia (UTHM) Terhadap Keselamatan dan Kesihatan Pekerjaan di Tempat Kerja - Samsuddin, Abas (2012)
The purpose of this study is to determine the level of awareness among engineering faculty UTHM staff towards occupational safety and health at the workplace. Questionnaires were used as the main instrument for obtaining data for this study. The data were analysed descriptively based on frequency, percentage and mean in order to determine the level of awareness of the respondents towards occupational safety and health at the workplace. To examine the relationship between demographic factors and respondents’ awareness towards occupational safety and health at the workplace, the Pearson Correlation was used. The results showed that engineering faculty UTHM staff had a high level of awareness of occupational safety and health at workplace based on their overall mean score of 4.09. Findings also showed that demographic factors did not influence the level of awareness, whether directly or indirectly. The factors that were analysed recorded a level of relationship of <0.20 and 0.20 – 0.40 only. This indicates a weak correlation. Finally, this study concludes that in order to raise the level of awareness towards occupational safety and health at workplace, the engineering faculty UTHM administration should increase the number of training programmes, safety and health awareness campaigns, offer continuous or periodic safety and health programmes and enforce the use of safety equipment by staff involved in high risk tasks. The results obtained are very important to improve and increase the level of awareness especially engineering faculty UTHM staff and generally, the entire UTHM staff on occupational safety and health at workplace.